The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1093/ajcn/65.6.1709
|View full text |Cite
|
Sign up to set email alerts
|

Body composition assessed on the basis of arm circumference and triceps skinfold thickness: a new index validated in children by magnetic resonance imaging

Abstract: Fat and muscle areas can be calculated from equations on the basis of upper arm circumference (C) and triceps skinfold thickness (TS). These equations assume a circular limb and muscle compartment and a symmetrically distributed fat rim: total upper arm area (TUA) = C2/(4 pi), upper arm muscle area (UMA) = [C - (TS x pi)2]/(4 pi), and upper arm fat area (UFA) = TUA - UMA. This traditional method underestimates the degree of adiposity. We propose that the unrolled fat rim is a rectangle whose length = C and wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
72
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 10 publications
3
72
0
1
Order By: Relevance
“…The use of the upper arm fat estimate, validated by magnetic resonance (Rolland-Cachera et al, 1997), is in agreement with our SUM data, although the reference values obtained in a small sample born during the 1950s were lower than those obtained in the same way in our study.…”
Section: Discussionsupporting
confidence: 90%
“…The use of the upper arm fat estimate, validated by magnetic resonance (Rolland-Cachera et al, 1997), is in agreement with our SUM data, although the reference values obtained in a small sample born during the 1950s were lower than those obtained in the same way in our study.…”
Section: Discussionsupporting
confidence: 90%
“…3,4 A few years ago we conducted a similar study, comparing anthropometry and magnetic resonance imaging (MRI) in obese and normal weight children. 5 We also found that the Jelliffe formula underestimated fat area in both groups and more markedly in the obese. Moreover, we proposed a simplified formula C Â (T/2) that we named the upper arm fat area estimate (UFE), and found its results very close to MRI data in both studied groups.…”
supporting
confidence: 53%
“…Circumferences measured at midarm, midthigh, waist and hip are used more frequently than others, because they indicate differences among people in major regions of the body. Recently, many studies have used circumferences for estimating skeletal muscle mass and fat distribution (Rolland-Cachera et al, 1997;Moreno et al, 1999).…”
Section: Discussionmentioning
confidence: 99%